2015
DOI: 10.3762/bjoc.11.203
|View full text |Cite
|
Sign up to set email alerts
|

Profluorescent substrates for the screening of olefin metathesis catalysts

Abstract: SummaryHerein we report on a 96-well plate assay based on the fluorescence resulting from the ring-closing metathesis of two profluorophoric substrates. To demonstrate the validity of the approach, four commercially available ruthenium-metathesis catalysts were evaluated in six different solvents. The results from the fluorescent assay agree well with HPLC conversions, validating the usefulness of the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…(3) The method provided information on the conversion of substrates in olefin metathesis. These important findings in our study suggest a method to overcome the drawbacks of the profluorescent substrate-based HTS method for olefin metathesis …”
supporting
confidence: 92%
See 1 more Smart Citation
“…(3) The method provided information on the conversion of substrates in olefin metathesis. These important findings in our study suggest a method to overcome the drawbacks of the profluorescent substrate-based HTS method for olefin metathesis …”
supporting
confidence: 92%
“…Despite its importance of olefin metathesis, only one fluorescence-based HTS method for olefin metathesis has been developed thus far. In 2015, Reuter et al reported a profluorescent substrate based HTS method that can be used to measure the catalytic efficiency of only ring-closing metathesis (RCM), one class of olefin metathesis, because the fluorescence of the profluoroscent substrate was induced through RCM. Therefore, this method has a critical limitation because it cannot be applied to other olefin metatheses or other substrates.…”
mentioning
confidence: 99%
“…To investigate the intracellular catalytic activity of the labelled metathesis catalysts in the microalgae cells, an established pro‐fluorescent substrate was chosen (Figure 2 b, black). [15] This non‐fluorescent precursor is very reactive in ring‐closing metathesis, yielding umbelliferone as product (Figure 2 b, blue) whose formation can readily be monitored via fluorescence intensities. For catalyst uptake, the microalgae were incubated with aqueous catalyst solutions (containing 0.5 v % of water‐miscible co‐solvent to dissolve the catalyst) and washed thoroughly prior to addition of the non‐fluorescent substrate to avoid formation of fluorescent product by potential extracellular catalyst in the surrounding medium (cf.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the intracellular catalytic activity of the labelled metathesis catalysts in the microalgae cells, an established pro‐fluorescent substrate was chosen (Figure 2b, black) [15] . This non‐fluorescent precursor is very reactive in ring‐closing metathesis, yielding umbelliferone as product (Figure 2b, blue) whose formation can readily be monitored via fluorescence intensities.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the intracellular catalytic activity of the labelled metathesis catalysts in the microalgae cells, an established pro-fluorescent substrate was chosen (Figure 2b, black). [15] This non-fluorescent precursor is very reactive in ring-closing metathesis, yielding umbelliferone as product (Figure 2b, blue) whose formation can readily be monitored via fluorescence intensities. For catalyst uptake, the microalgae were incubated with aqueous catalyst solutions (containing 0.5 v % of water-miscible co-solvent to dissolve the catalyst) and washed thoroughly prior to addition of the non-fluorescent substrate to avoid formation of fluorescent product by potential extracellular catalyst in the surrounding medium (cf.…”
Section: Catalyst Uptake and In Cell Catalytic Activitymentioning
confidence: 99%